Affinities : Festspielausstellung 1989. (Salzburg : Galerie Academia, 1989)
Kogan, Nina ; Klee, Paul ; Breustedt, Hans Joachim ; Boeckl, Herbert ; Poliakoff, Serge ; Kostner, Arthur ; Bissier, Jules ; Rainer, Arnulf ; Leger, Fernand ; Messensee, Jürgen ; Alechinsky, Pierre ; Fischer, Lothar ; Miro, Joan ; Dubuffet, Jean ; Giacometti, Alberto ; Bischoffshausen, Hans ; Appel, Karel ; Voss, Jan ; Nitsch, Hermann ; Tinguely, Jean
Affinities : Festspielausstellung 1989, Galerie Academia, Salzburg, 1989
boek